Ecofeminism in A Thousand Splendid Suns: The Intertwining of Nature and Women’s Destiny - Guo, Huiyu (International Journal of Social Sciences and Public Administration, 2024)
This paper will provide an in-depth analysis of the long novel A Thousand Splendid Suns by Afghan-American writer Khaled Hosseini from the perspective of ecofeminism. By exploring the relationship between women and nature, women and society, and women and self in the novel, it reveals the embodiment of ecofeminism in the work, and then analyses how the novel reflects the realistic dilemmas of the Afghan society and women’s state of existence with the help of the perspective of ecofeminism.